Friction and Wear Response of Friction Stir Processed Cu/ZrO2 Surface Nano-Composite. (15th October 2022) - Kumar, Harikishor; Prasad, Rabindra; Kumar, Parshant; Hailu, Solomon Aynalem
Abstract : The present work aims to develop Cu/ZrO2 surface composite by friction stir processing and analyse the effect of zirconia incorporation on microstructure, mechanical, and tribological behaviour of developed copper matrix composite. Microstructural observations indicated that grains were equiaxed and fine in the stir zone of the composite and zirconia particles were uniformly dispersed in the copper matrix with excellent bonding. The test results for mechanical and wear behaviour showed increment in hardness and wear resistance as compared to copper which may be because of the effect of zirconia presence and grain refinement. The fabricated composite displayed higher value of average friction coefficient in comparison to as received copper. The worn surface observed by SEM revealed the predominance of adhesion and delamination wear mechanism in base copper.